Multicentric Invasive Pleomorphic Lobular Carcinoma of Breast: An Uncommon Histopathological Variant - Jagtap, Sunil V; Agarwal, Garima; Jagtap, Swati S (Annals of Pathology and Laboratory Medicine, 2020)
Invasive Pleomorphic Lobular Carcinoma is a very rare histopathological variant of breast cancer. It constitutes less than 1% of invasive breast carcinoma .We present a 70 year female presented with lump in right breast of 10 months duration. The lump was insidious in onset, progressive in nature and was associated with gradual skin color changes. Patient was a known diabetic and was on regular treatment. On fine needle aspiration cytology showed positive for carcinoma cells. Right modified mastectomy was performed. On histopathology reported as Invasive Pleomorphic Lobular Carcinoma – Grade II with multicentric nodules. Right axillary lymph nodes with perinodal infiltration of tumor were noted. We are presenting this case for its uncommon type, clinical, histomorphological and immunohistochemistry pattern.